2004
DOI: 10.1117/1.1695563
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of enhanced tissue features in narrow-band endoscopic imaging

Abstract: This study was performed to examine the usefulness of medical endoscopic imaging utilizing narrow-band illumination. The contrast between the vascular pattern and the adjacent mucosa of the underside of the human tongue was measured using five narrow-band illuminations and three broadband illuminations. The results demonstrate that the pathological features of a vascular pattern are dependent on the center wavelength and the bandwidth of illumination. By utilizing narrow-band illumination of 415+/-30 nm, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
562
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(578 citation statements)
references
References 19 publications
5
562
0
11
Order By: Relevance
“…In contrast, WLI has poor performance, low sensitivity, and low specificity. By means of ME-NBI examination, one is immediately able to observe suspicious lesions in higher magnification, and can clearly see the micromorphology and the microvascular structure of mucosal lesions to identify cancerous lesions [24,25]. Currently, the ''VS classification'' criteria of Yao et al [26,27], which suggest the presence of a lesion with the boundary, an abnormal vascular network on its surface, or an abnormal change on the surface of the microstructure, are widely used as the diagnostic criteria for ME-NBI diagnosis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, WLI has poor performance, low sensitivity, and low specificity. By means of ME-NBI examination, one is immediately able to observe suspicious lesions in higher magnification, and can clearly see the micromorphology and the microvascular structure of mucosal lesions to identify cancerous lesions [24,25]. Currently, the ''VS classification'' criteria of Yao et al [26,27], which suggest the presence of a lesion with the boundary, an abnormal vascular network on its surface, or an abnormal change on the surface of the microstructure, are widely used as the diagnostic criteria for ME-NBI diagnosis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the performance of ME-NBI is also affected by the blood and bile in the stomach. Since the working principle of narrow band imaging is based on the strong absorption of narrow band light by hemoglobin and the high reflection of mucosal surfaces, blood and bile on the surface of lesions may result in failure of ME-NBI observation [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…12). 36 Combining the NBI and magnifying endoscopy (M-NBI) visualized contrasted micromucosal structures and microvascular architecture of the superficial mucosa. 37 Tahara et al 38 classified M-NBI images of the gastric mucosa into four groups and showed that sensitivity and specificity of the type 3 pattern for IM were 73.3% and 95.6%, respectively (Fig.…”
Section: Atrophic Gastritis In Magnifying Chromoendoscopy and Narrowmentioning
confidence: 99%
“…Studies of combinations of different wavelengths showed that a combination of 415 and 540 nm provided the highest visibility. Therefore, the current NBI system uses these two wavelengths (7).…”
Section: Technical Background Of Narrow Band Imagingmentioning
confidence: 99%